The impact of changes to national hypertension guidelines on hypertension management and outcomes in the UK - Lay-Flurrie, S; Sheppard, J; Stevens, R; Mallen, C; Heneghan, C; Hobbs, F; Williams, B; Mant, J; McManus, R (American Heart Association, 2019)
In recent years, national and international guidelines have recommended the use of out-of-office blood pressure monitoring for diagnosing hypertension. Despite evidence of cost-effectiveness, critics expressed concerns this would increase cardiovascular morbidity. We assessed the impact of these changes on the incidence of hypertension, out-of-office monitoring and cardiovascular morbidity using routine clinical data from English general practices, linked to inpatient hospital, mortality, and socio-economic status data. We studied 3 937 191 adults with median follow-up of 4.2 years (49% men, mean age=39.7 years) between April 1, 2006 and March 31, 2017. Interrupted time series analysis was used to examine the impact of changes to English hypertension guidelines in 2011 on incidence of hypertension (primary outcome). Secondary outcomes included rate of out-of-office monitoring and cardiovascular events. Across the study period, incidence of hypertension fell from 2.1 to 1.4 per 100 person-years. The change in guidance in 2011 was not associated with an immediate change in incidence (change in rate=0.01 [95% CI, −0.18–0.20]) but did result in a leveling out of the downward trend (change in yearly trend =0.09 [95% CI, 0.04–0.15]). Ambulatory monitoring increased significantly in 2011/2012 (change in rate =0.52 [95% CI, 0.43–0.60]). The rate of cardiovascular events remained unchanged (change in rate =−0.02 [95% CI, −0.05–0.02]). In summary, changes to hypertension guidelines in 2011 were associated with a stabilisation in incidence and no increase in cardiovascular events. Guidelines should continue to recommend out-of-office monitoring for diagnosis of hypertension.